Enhanced neural responsiveness to reward associated with obesity in the absence of food‐related stimuli. Issue 6 (20th February 2015) - Opel, Nils; Redlich, Ronny; Grotegerd, Dominik; Dohm, Katharina; Haupenthal, Cordula; Heindel, Walter; Kugel, Harald; Arolt, Volker; Dannlowski, Udo
Abstract Background Obesity has been characterized by alterations in brain structure and function associated with emotion processing and regulation. Particularly, aberrations in food‐related reward processing have been frequently demonstrated in obese subjects. However, it remains unclear whether reward‐associated functional aberrations in obesity are specific for food‐related stimuli or represent a general deficit in reward processing, extending to other stimulus domains. Given the crucial role of rewarding effects in the development of obesity and the ongoing discussion on overlapping neurobiological traits of obesity and psychiatric disorders such as depression and substance‐related disorders, this study aimed to investigate the possibility of altered reward processing in obese subjects to occur in the absence of food‐related stimuli during a monetary reward condition. Methods Twenty‐nine healthy obese subjects (body mass index >30) and 29 healthy, age‐, and sex‐matched control subjects of normal weight underwent functional MRI during a frequently used card guessing paradigm. A Group × Condition (win vs. loss) ANOVA was conducted to investigate differences between obese and normal‐weight subjects. Results We found significant Group × Condition interaction effects in brain areas involved in emotion regulation and reward processing including the insula, the striatum, and the orbitofrontal cortex (OFC). This interaction was predominantly driven by a significant increase in blood oxygenation level dependent (BOLD) response in obese individuals while experiencing reward. Conclusions Enhanced neural activation in obesity during reward processing seems to be apparent even in the absence of food‐related stimuli and, thus, might point to generalized dysfunctions in reward‐related brain circuits in obese individuals. Hum Brain Mapp 36:2330–2337, 2015. © 2015 Wiley Periodicals, Inc.